Adenocarcinoma of Rete Testis - 曹唐義(Tang-Yi Tsao); 黃鐘銘(Zhon-Min Huang); 童敏哲(Min-Zhe Tung); 陳志強(Chee-chiang Chen) (童綜合醫學雜誌, 2018)
A 57 year old male presented out-patient department of urology, with a chief complaint of intermittent dull pain in the right lower quadrant for 4 weeks. Physical examination, revealed a 2 x 2 cm, tender, movable right inguinal mass. Ultrasound revealed a right inguinal undescended testis with testicular and epididymis atrophy. He was admitted for orchiectomy of the undescended testis. His serum α-fetoprotein and human chorionic gonadotropin levels were normal but his CEA levels (11.2 ng/ml) were slightly elevated. He was pathologically diagnosed with adenocarcinoma of rete testis of the right testis. Postoperative abdominal computed tomogralhy and FDG PET scan revealed numerous peritoneal and mesenteric metastatic nodules. We reviewed the literature and discussed pathologic findings and clinical behavior of adenocarcinoma of rete testis.